The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1590/s1516-35982003000500028
|View full text |Cite
|
Sign up to set email alerts
|

Composição químico-bromatológica, produção de gás, digestibilidade in vitro da matéria seca e NDT estimado da silagem de sorgo com diferentes proporções de panículas

Abstract: RESUMO -Foram objetivos do presente trabalho avaliar as alterações na composição bromatológica, nas frações nitrogenadas e de carboidratos, estimar a taxa de digestão dos carboidratos fibrosos (CF) e não-fibrosos (CNF), determinar a digestibilidade in vitro da matéria seca (DIVMS) e estimar o NDT da silagem de sorgo com as seguintes proporções de panículas: 0, 20, 40, 60, 80 e 100%. Foram determinados os teores de matéria seca (MS), proteína bruta (PB), extrato etéreo (EE), matéria mineral (MM), fibra em deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
4
9
2
2
Order By: Relevance
“…The values observed in this study corroborated with the literature data (Rocha Jr. et al, 2000;Cândido et al, 2002;Molina et al, 2002;Rodrigues et al, 2002;Neumann et al, 2005;Skonieski et al, 2010).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The values observed in this study corroborated with the literature data (Rocha Jr. et al, 2000;Cândido et al, 2002;Molina et al, 2002;Rodrigues et al, 2002;Neumann et al, 2005;Skonieski et al, 2010).…”
Section: Resultssupporting
confidence: 92%
“…The average concentration of CP was 6.47 dag/kg DM in the silage hybrids, higher than those observed by Skonieski et al (2010) and Cabral et al (2003), of 6.10 and 5.53 dag/kg DM, respectively. For Neumann et al (2002b), variations in the proportion of stems, leaves, and panicles of sorghum plants are the main responsible for variations in the protein content between different hybrids, since the appropriate fermentation profile minimizes losses of nutrients during the fermentation process.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Cabral et al (2003), evaluated the nutritive value of sorghum silages and observed a linear increase in DM content with an increment in panicle ratio, which helps to explain the results obtained.…”
Section: Resultsmentioning
confidence: 85%
“…These high values for VF1 are due to the higher NFC content presented by these genotypes (Table 2), conferring greater availability of fermentable substrate and providing greater gas production for this fraction. Degradation rates for the rapidly degradable fraction (C1) were low, averaging 0.068/h, since reports of values from 0.1 to 0.2/h, are frequent (Cabral et al, 2003;Senger et al, 2007;Detmann et al, 2009). The highest gas productions from the fermentation of the slowly degradable fraction (VF2) were found for accessions 31828 and 31534.…”
Section: Resultsmentioning
confidence: 99%